"Blessing in disguise": The impact of the Wenchuan earthquake on inbound tourist arrivals in Sichuan, China. (March 2020) - Huang, Li; Yin, Xin; Yang, Yang; Luo, Mingzhi; Huang, Songshan (Sam)
Abstract: By analysing the long-term effect of the Wenchuan earthquake on inbound tourist arrivals in Sichuan, this study probes the long-term recovery of inbound tourist arrivals in disaster areas. Empirical evidence reveals the existence of a "Blessing in Disguise" effect, as the growth of overall inbound tourist arrivals to Sichuan after the earthquake has significantly increased. Moreover, we show that this "blessing in disguise" effect is a specific phenomenon, contrasting with China's overall inbound tourism during the same period. This study contributes to the overall knowledge of post-disaster tourism recovery. Managerial implications for post-disaster tourism destinations are discussed.